House price volatility and the housing ladder - James Banks; Richard Blundell; Zoë Oldfield; James P. Smith (Institute for the Study of Labor (IZA), 2010)
This paper investigates the effects of housing price risk on housing choices over the lifecycle. Housing price risk can be substantial but, unlike other risky assets which people can avoid, the fact that most people will eventually own their home creates an insurance demand for housing assets early in life. Our contribution is to focus on the importance of home ownership and housing wealth as a hedge against future house price risk for individuals moving up the ladder - people living in places with higher housing price risk should own their first home at a younger age, should live in larger homes, and should be less likely to refinance. These predictions are tested and shown to hold using panel data from the United States and Great Britain.
Keywords: D12; D91; 330; downsizing; migration; Immobilienpreis; Volatilität; Wohneigentum; Lebensverlauf; Wohnungswechsel; Großbritannien; USA